The pragmatics of exhaustivity in embedded questions: an experimental comparison of know and predict in German and English - Fricke, Lea; Destruel, Emilie; Zimmermann, Malte; Onea, Edgar (Frontiers in Psychology, 2023)
We present a cross-linguistic experimental study investigating the exhaustivity properties of questions embedded under wissen/to know and korrekt vorhersagen/to correctly predict in German and English. The past theoretical literature has held a very influential position regarding the interpretation of such embedded questions: They should only be interpreted as strongly exhaustive (SE). So, for example, the utterance "Ali knows who danced at the party" necessarily conveys that Ali not only knows all the people who danced but also that they were the only ones who danced.Yet, recent experimental research challenged this view, showing that an intermediate exhaustive (IE) interpretation is possible, and in fact dominant. In that case, the utterance above is true if Ali knows who danced and does not have false beliefs about any non-dancers. In this paper, we explore the puzzle of the discrepancy between introspection and experimental findings by investigating the pragmatic likelihood of the different readings. Participants were confronted with a decision problem involving the different exhaustive readings, and they received a financial incentive based on their performance. Crucially, they had to assess whether their interpretations would be shared by other speakers. We created probabilistic models of the participants' beliefs in a Bayesian analysis, with a linking hypothesis between participants' responses and readings based on utility maximization in simple decision problems.For wissen/to know, we found SE readings to have the highest probability in both languages, in line with the judgments in the early theoretical literature; IE readings were attested too, but we did not replicate the results of previous experiments.For German korrekt vorhersagen, the IE-reading clearly had the highest probability, whereas for English to correctly predict we found a preference for the SE reading. This cross-linguistic difference correlates with independent evidence from corpus data, which indicate that German vorhersagen and English to predict are not fully equivalent in lexical meaning. By including an explicit pragmatic component, our 1 study complements previous approaches, which focused on the mere availability of a given reading.